Performance enhancement strategy through work engagement: the role of transformational leadership and structural empowerment / Nurhidayati and Najmah - -, Nurhidayati; -, Najmah (2022)
Having a strategy to enhance human resource performance is important for every organization in order to ensure its sustainability in a global, competitive world. Organization needs to recognize the key factors which play fundamental roles in improving performance so that the efforts are effective and right on target. Transformational leadership and structural empowerment are two factors which have vital roles. The aim of this study is to analyze the effect of transformational leadership and structural empowerment on human resource performance through work engagement. The population in this study were employees in a furniture manufacturing company in Semarang, Central Java, Indonesia. The sampling technique employed in this study was purposive random sampling with 100 respondents and it used questionnaire as a research instrument. Partial Least Square (PLS) was used as data analysis technique. The results showed that transformational leadership and structural empowerment have positive and significant effect on work engagement and human resource performance. Work engagement was also found to mediate the influence of transformational leadership and structural empowerment on human resource performance.